Perspectives of researchers and clinicians on patient and public involvement (PPI) in preclinical spinal cord research: An interview study - Pádraig Carroll; Éimear Smith; Adrian Dervan; Ciarán McCarthy; Cliff Beirne; John Quinlan; Geoff Harte; Dónal O'Flynn; Fergal J. O'Brien; Frank Moriarty; Michelle Flood (Wiley, 2024)
Abstract Introduction Patient and public involvement (PPI) in research is an embedded practice in clinical research, however, its role in preclinical or laboratory‐based research is less well established and presents specific challenges. This study aimed to explore the perspectives of two key stakeholder groups, preclinical researchers and clinicians on PPI in preclinical research, using spinal cord research as a case study. Methods Semi‐structured interviews were conducted online with 11 clinicians and 11 preclinical researchers all working in the area of spinal cord injury (SCI). Interviews were transcribed verbatim and analysed thematically. Findings Nine themes were developed through analysis. Participants' perspectives included that people living with SCI had a right to be involved, that PPI can improve the relevance of preclinical research, and that PPI can positively impact the experiences of researchers. They identified the distance between lab‐based research and the daily experiences of living with SCI to be a barrier and proactive management of accessibility and the motivated and networked SCI community as key facilitators. To develop strong partnerships, participants suggested setting clear expectations, ensuring good communication, and demonstrating respect for the time of PPI contributors involved in the research. Conclusions While traditionally PPI has been more commonly associated with clinical research, participants identified several potential benefits of PPI in preclinical spinal cord research that have applicability to preclinical researchers more broadly. Preclinical spinal researchers should explore how to include PPI in their work. Patient or Public Contribution This study was conducted as part of a broader project aiming to develop an evidence base for preclinical PPI that draws on a 5‐year preclinical research programme focused on the development of advanced biomaterials for spinal cord repair as a case study. A PPI Advisory Panel comprising seriously injured rugby players, clinicians, preclinical researchers, and PPI facilitators collaborated as co‐authors on the conceptualisation, design of the interview protocol, data analysis and writing of this manuscript.